Response of grassland vegetation composition to different fertilizer treatments recorded over ten years following 64 years of fertilizer applications in the Rengen Grassland Experiment. Issue 3 (31st May 2020) - Titěra, Jan; Pavlů, Vilém V.; Pavlů, Lenka; Hejcman, Michal; Gaisler, Jan; Schellberg, Jürgen
Abstract: Questions: Fertilizer application is a key driver affecting the diversity and conservation value grassland vegetation. Using a long‐term fertilization experiment in mountain grassland, we addressed the following questions: (a) what is the effect of long‐term fertilizer applications on species richness and plant species composition, and (b) is there any detectable trend in plant species composition during ten years of continuous observation? Location: The Rengen Grassland Experiment, Eifel Mountains, Germany (established in 1941). Methods: Five treatments including different fertilizers applied annually and one unfertilized control were analysed: Ca (718 kg Ca ha −1 ); CaN (752 Ca and 100 N kg ha −1 ); CaNP (752 Ca, 100 N and 35 P kg ha −1 ); CaNP‐KCl (752 Ca, 100 N, 35 P and 133 K kg ha −1 ); CaNP‐K2 SO4 (752 Ca, 100 N, 35 P and 133 K kg ha −1 ). The experiment included five replicates per treatment in a fully randomized block design. All treatments were cut twice a year in late June or early July, and in mid‐October. Percentage cover of individual plant species was estimated by visual observation in each plot in late June in the years 2005–2014. Results: Despite inter‐annual variability in the cover of the individual vascular plant species, the multivariate data analyses revealed a relatively similar response of the plant community to the different fertilizer applications throughout the ten years. With phosphorus application, no differences in botanical composition among treatments were found; however, they did differ from other treatments without phosphorus application. In the unfertilized control, there was a certain directed trend in plant species composition in response to ongoing nutrient impoverishment. Conclusion: Species‐rich grasslands of high nature conservation value were only maintained under P limitation in the control without fertilizer application ( Violion caninae ) and in the liming treatment ( Polygono‐Trisetion ), but also in the treatment with liming and pure N addition. It seems that after 74 years, some stage of equilibrium of the grassland community was achieved in all treatments receiving any type of fertilizer application, but less so in the unfertilized control treatment. Abstract : Species‐rich grasslands of high nature conservation value were only maintained under P limitation in the control without fertilizer application and in the liming treatment, but also in the treatment with liming and pure N addition. It seems that after 74 years, some stage of equilibrium of the grassland community was achieved in all treatments receiving any type of fertilizer application.